Year zero of the Arab-Israeli conflict 1929 - Cohen, Hillel, 1961- (Waltham, Massachusetts)
xxi, 288 s.
Keywords: "In late summer 1929 a country-wide outbreak of Arab-Jewish-British violence transformed the political landscape of Palestine forever. As against those who point to the wars of 1948 or 1967, Hillel Cohen marks these bloody events as year zero of the Arab-Israeli conflict that persists until today. The murderous violence inflicted on the Jews caused a fractious, but now traumatized, community comprised of Zionists, non-Zionists, Ashkenazim and Mizrahim to coalesce around a unified national consciousness arrayed against an implacable Arab enemy. As the Jews unified, Arabs came to grasp the national essence of the conflict and realized that Jews of all stripes viewed the land as belonging to the Jewish people. In a manner both associative (memory) and also highly calculated (historiography), Cohen traces the horrific events of August 23 to September 1 in painstaking detail. He extends his geographic and chronological reach to what came before and after, while his non-linear reconstruction of events calls for a reconsideration of cause and effect. Sifting through Arabic and Hebrew sources, many rarely if ever examined before, Cohen reflects on the attitudes and perceptions of Jews and Arabs who experienced the events and, most significantly, the memories they bequeathed to later generations. The result is a multifaceted and revealing examination of a formative series of episodes that will intrigue historians, political scientists, and other interested in understanding the essence - and very beginning - of what has been an intractable conflict." --